Pattern of Leprosy: A Histomorphological Study with Clinical Correlation in Ajmer District - Menghani, Bhawika; Gupta, Abha; Kasliwal, Neena; Gupta, Rahul (Annals of Pathology and Laboratory Medicine, 2021)
Background: Leprosy (Hansen’s disease) still continues to be an important public health problem. The present study was carried to correlate histological diagnosis of skin biopsies of untreated leprosy cases with clinical diagnosis using Ridley- Jopling classification. Material and Methods: 124 skin biopsies of untreated leprosy cases over a period of 6 years were included. Paraffin sections of biopsies were stained with Haematoxylin & Eosin, Ziehl- Neelsen’s & Fite stains examined and classified histopathologically according to Ridley- Jopling scale and then correlated with clinical diagnosis. Results: Prevalence rate of leprosy in Ajmer district is 0.16 per 10,000 population per annum. Among the 124 biopsies, most cases were of indeterminate type (39.51%), followed by LL type (17.74%), TT type (16.93%), BT type (10.48%), BL type (07.25%), BB type (05.64%), histioid type (2.41%). Most commonly the patients were affected in 4th decade of life. Male and female ratio was 2.26:1. Most common clinical presentation was anesthesia. Conclusion: Correlation of clinical and histopathological features along with bacteriological index appears more useful for accurate typing of leprosy than considering any of the single parameters alone. This helps the clinician for better care and management of the patients.